Metal member, metal-resin composite, method for manufacturing metal member, and method for manufacturing metal-resin composite
By forming a nano-column structure on the surface of the metal member and filling it with resin, the problem of insufficient sealing ability of the metal member and the resin member is solved, and a higher sealing effect is achieved.
Patent Information
- Application Number
- CN202410447175.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-07
- Filing Date
- 2024-04-15
- Publication Date
- 2025-01-14
AI Technical Summary
The sealing property is insufficient when the conventional metal member is engaged with the resin member, and it is desirable to further improve the sealing property.
The roughened area is formed on the surface of the metal member, including a base layer and a column group layer. The base layer is formed by a pile of fragmented particles. The column group layer is composed of nanocolumns whose fragmented particles are bound in a rosary connection and extend in a height direction. The average height of the body is above 84 nm, these structures are generated by pulsed laser irradiation, and the hot melt resin is filled into the gap between the nanocolumns until it reaches the base layer, and then cured to improve sealing.
The sealing property of the metal member when bonding with the resin member is significantly improved, and the formed metal resin composite can effectively seal the first space and the second space, enhancing the overall sealing performance.
Smart Images

Figure CN119315186A_ABST
Abstract
Description
Technical Field
[0001] The technical field disclosed in this specification relates to a metal member, a metal-resin composite, a method for producing a metal member, and a method for producing a metal-resin composite. Background Art
[0002] A metal-resin composite formed by bonding a metal component to a resin component is known. In order to improve the sealing performance between the metal component and the resin component, the surface of the metal component is roughened in advance, for example, using a laser or the like. As a related prior art, for example, Patent Document 1 can be cited.
[0003] Patent Document 1 describes forming a nano-recess on the surface of a metal component, the nano-recess having a submicron-level or nanometer-level opening width L and a depth D. Specifically, the nano-recess is formed in such a manner that the relationship between the opening width L and the depth D is D / L ≥ 1. That is, a protrusion is formed on the surface of the metal component, and the length and shape of the protrusion cannot be said to be a columnar portion as a whole.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2018-75805 Summary of the invention
[0007] Problems to be solved by the invention
[0008] However, in the case of conventional metal members being joined to resin members, the sealing performance at the joint portion is insufficient, and further improvement of the sealing performance is desired.
[0009] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide a metal component and a method for manufacturing the metal component having excellent sealing properties at the joint portion when joined with a resin component, as well as a metal-resin composite having excellent sealing properties and a method for manufacturing the metal-resin composite.
[0010] Means for solving problems
[0011] In order to solve the above-mentioned problems, a metal component of one embodiment of the present invention is a metal component having a joining area on the surface, wherein the joining area is joined to a resin component and together with the resin component seals the first space and the second space, wherein the joining area includes a roughened area formed on the surface, wherein the roughened area is formed with a base layer and a column group layer, wherein the base layer is a layer formed by accumulation of fragment particles, and the column group layer is a layer in which the fragment particles are connected in a rosary-like manner and nano-columns extending from the base layer in a height direction are two-dimensionally arranged, and the average height of the nano-columns in the roughened area is greater than 84 nm.
[0012] According to the metal component of the present invention, a joining area is formed on the surface of the metal component. When the metal component is combined with other metal components via a resin component, the joining area is joined with the resin component to seal the metal component with other metal components. The joining area includes a roughened area, and the roughened area forms a base layer formed by accumulation of fragment particles, and a column group layer in which the fragment particles are connected in a rosary-like manner and nano-columns extending from the base layer in a height direction are two-dimensionally arranged. The average height of the nano-columns in the roughened area is 84 nm, and therefore, the sealing of the joining portion when combined with the resin component can be improved.
[0013] A metal-resin composite according to another aspect of the present invention includes the above-mentioned metal member and a resin member bonded to the bonding region, wherein the resin forming the resin member fills the gaps between the nano columnar bodies until reaching the base layer.
[0014] According to another embodiment of the present invention, the manufacturing method of the above-mentioned metal component includes: a laser irradiation process, wherein, on the surface of the metal component that can become the roughened area in a state where the column group layer has not yet been formed, fragment particles from the metal component generated by irradiation of pulsed laser are accumulated and grown into the nano-columnar bodies, thereby forming the roughened area.
[0015] Furthermore, according to another embodiment of the present invention, the manufacturing method of the above-mentioned metal-resin composite includes: a filling process, wherein hot-melted molten resin is filled into the gaps between the nano-columns forming the column group layer until it reaches the base layer; and a curing process, wherein the molten resin filled into the gaps between the nano-columns forming the column group layer in the filling process is solidified to form a resin component bonded to the roughened area. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a perspective view of a battery according to an embodiment.
[0017] Figure 2 for Figure 1 AA cross-section diagram.
[0018] Figure 3 A three-dimensional diagram of a positive terminal component.
[0019] Figure 4 For Figure 1 A perspective view of a unit component with a battery extracted.
[0020] Figure 5A for Figure 4 BB cross-section diagram.
[0021] Figure 5B for Figure 4CC cross-section diagram.
[0022] Fig. 6A It is an explanatory diagram for explaining the bonding region between the upper surface of the cover member and the positive electrode resin member, and the region on the upper surface of the cover member to which the roughening treatment is applied.
[0023] Figure 6B It is an explanatory diagram for explaining the bonding region between the lower surface of the cover member and the positive electrode resin member, and the region on the lower surface of the cover member to which the roughening treatment is applied.
[0024] Fig. 7A It is an explanatory diagram for explaining a bonding region between a side surface of a part of a positive electrode terminal member and a positive electrode resin member, and a region on the side surface of a part of a positive electrode terminal member to which a roughening treatment has been applied.
[0025] Figure 7B It is an explanatory diagram for explaining the bonding region between the lower surface of the long straight portion of the positive electrode terminal member and the positive electrode resin member, and the region on the lower surface of the long straight portion of the positive electrode terminal member that has been subjected to a roughening treatment.
[0026] Figure 8 This is an image showing how the foundation layer and the column group layer are actually formed.
[0027] Fig.9A This is an image showing how the resin (polyphenylene sulfide) of the positive electrode resin member actually fills the gaps between the nanocolumnar bodies.
[0028] Fig. 9B This is an image showing how the resin (polyphenylene sulfide) of the positive electrode resin member actually fills the gaps between the nanocolumnar bodies.
[0029] Fig.10 This is a flow chart of a method for manufacturing a battery according to an embodiment.
[0030] Fig.11A FIG. 1 is a diagram schematically showing a roughening process for the roughened area on the lower surface of the cover.
[0031] Fig. 11B A diagram schematically showing the roughening process of the roughened area on the side surface of the terminal.
[0032] Fig.12 A diagram schematically illustrating an insert molding process.
[0033] Fig.13A , 13B This is an explanatory diagram schematically showing a test specimen.
[0034] Fig.14TABLE 4 is a table showing the relationship between various conditions of pulse laser irradiation on the roughened region and the average height and surface area ratio of the nanocolumnar bodies formed in the roughened region.
[0035] Fig.15A This is a scatter plot with the horizontal axis representing the average height of the nanocolumns and the vertical axis representing the helium leakage rate.
[0036] Fig. 15B This is a scatter plot with the horizontal axis representing the surface area ratio and the vertical axis representing the helium leakage rate.
[0037] Fig.16A This is an example of a cross-sectional image of a cross-sectional sample obtained using a scanning electron microscope.
[0038] Fig. 16B Based on Fig.16A An explanatory diagram illustrating the cross-sectional area and bottom length of a nanocolumnar body.
[0039] Description of Reference Numerals
[0040] 1…battery, 10…housing, 20…main body member, 30…cover member, 33h…positive electrode insertion hole, 34h…negative electrode insertion hole, 50…positive electrode terminal member, 60…negative electrode terminal member, 70…positive electrode resin member, 80…negative electrode resin member, 35, 55…base layer, 36, 56…column group layer, 361, 561…nano columnar body, E1…cover upper surface bonding region, E2…cover lower surface bonding region, E3…terminal side bonding region, E4…terminal lower surface bonding region, F1…cover upper surface roughening region, F2…cover lower surface roughening region, F3…terminal side roughening region, F4…terminal lower surface roughening region DETAILED DESCRIPTION
[0041] The following is an explanation of the embodiments of the present invention with reference to the accompanying drawings. The battery 1 constituting the metal-resin composite of the present invention is an example of an electrical storage device, specifically, a square and sealed lithium-ion secondary battery mounted on vehicles such as hybrid vehicles, plug-in hybrid vehicles and electric vehicles. Furthermore, the reference numerals X, Y, and Z related to the directions in the following drawings are reference numerals for limiting directions, indicating the left-right direction, the front-back direction, and the up-down direction. In addition, the reference numerals U, D, L, R, F, and B recorded at the positions of the arrows related to the directions are reference numerals for limiting positions, indicating the upper side, the lower side, the left side, the right side, the front side, and the rear side. However, these directions and positions are limited for the convenience of explanation. Therefore, there is no limitation on the direction in which the battery 1 is set.
[0042] [Battery composition]
[0043] Figure 1 It is a three-dimensional diagram of the battery 1. Figure 2 for Figure 1 AA section diagram in. Figure 1 and Figure 2 As shown, the battery 1 includes a case 10 that seals the interior, an electrode body 40 housed in the case 10 , and a positive terminal member 50 and a negative terminal member 60 connected to an electrolyte 3 , an insulating holder 5 , and the electrode body 40 .
[0044] The shell 10 is generally flat and has a bottomed rectangular parallelepiped shape. In the present embodiment, the shell 10 is made of aluminum. However, the material of the shell 10 is not limited to aluminum, and is preferably made of metal. For example, the material of the shell 10 may be other metals such as aluminum alloy, iron and iron alloy. In addition, the shell 10 is composed of a main body member 20 and a cover member 30. The cover member 30, the positive terminal member 50, and the negative terminal member 60 are examples of the "metal member" of the present invention.
[0045] The main body member 20 is formed into a bottom square tube. In addition, the main body member 20 has an opening 21. In other words, the main body member 20 has: a rectangular plate-shaped bottom 12, a pair of front side portions 13 and rear side portions 14 vertically erected from the edge of the front side F and the edge of the rear side B of the bottom 12, and a pair of left side portions 15 and right side portions 16 vertically erected from the end of the left side L and the end of the right side R of the bottom 12. The shape of the opening 21 is a rectangle with the left-right direction X as the long side direction and the front-back direction Y as the short side direction. The shape of the bottom 12 is a rectangular plate with the left-right direction X as the long side direction and the front-back direction Y as the short side direction. The shape of the front side portion 13 and the rear side portion 14 is a rectangular plate with the left-right direction X as the long side direction and the up-down direction Z as the short side direction. The shape of the left side portion 15 and the right side portion 16 is a rectangular plate with the up-down direction Z as the long side direction and the front-back direction Y as the short side direction.
[0046] Furthermore, the height (length in the vertical direction Z) of the front side portion 13 and the rear side portion 14 is the same as the height (length in the vertical direction Z) of the left side portion 15 and the right side portion 16. In addition, the height (length in the vertical direction Z) of the front side portion 13 and the rear side portion 14 and the length in the horizontal direction X of the front side portion 13 and the rear side portion 14 are considerably longer than the length in the front-back direction Y of the left side portion 15 and the right side portion 16. Therefore, hereinafter, with respect to the housing 10, the main body member 20 and the cover member 30, the horizontal direction X is sometimes referred to as the "length direction", the front-back direction Y is referred to as the "width direction", and the vertical direction is referred to as the "height direction".
[0047] The cover member 30 closes (seales) the opening 21 of the main body member 20. Specifically, the peripheral edge of the cover member 30 is laser welded to the top end of the upper side U of the front side portion 13, the rear side portion 14, the left side portion 15, and the right side portion 16 over the entire circumference (entire circumference). Furthermore, at the boundary portion between the top end of the main body member 20 and the peripheral edge of the cover member 30, a molten solidified portion 18 where the main body member 20 and the cover member 30 are melted and solidified is formed over the entire circumference by laser.
[0048] A safety valve 19 is provided slightly to the left L of the center of the cover member 30 in the left-right direction X. The safety valve 19 breaks and opens when the internal pressure of the housing 10 exceeds the valve opening pressure. A liquid injection hole 30k is formed slightly to the right R of the center of the cover member 30 in the left-right direction X, which penetrates the cover member 30 in the up-down direction Z. A sealing member 39 made of aluminum is fitted into the liquid injection hole 30k from the upper side U, thereby hermetically sealing the liquid injection hole 30k.
[0049] On one side of the cover member 30 in the left-right direction X ( Figure 1 , Figure 2 A positive electrode insertion hole 33h is formed near the end portion of the left side L in the middle of the cover member 30, which penetrates the cover member 30 in the vertical direction Z. In addition, at the other side ( Figure 1 , Figure 2 Near the end portion (R) on the right side of the middle, a negative electrode insertion hole 34h is formed that penetrates the cover member 30 in the up-down direction Z. The positive electrode insertion hole 33h and the negative electrode insertion hole 34h are formed into a rectangle with the left-right direction X as the long side direction and the front-to-back direction Y as the short side direction. The positive terminal member 50, which is a longitudinal shape as a whole (extending in one direction), is inserted into the positive electrode insertion hole 33h from the upper side U along its length direction. The negative terminal member 60, which is a longitudinal shape as a whole (extending in one direction), is inserted into the negative electrode insertion hole 34h from the upper side U along its length direction.
[0050] The positive terminal member 50 is fixed to the cover member 30 via the positive electrode resin member 70 in a state of being insulated from the cover member 30. Therefore, the positive terminal member 50 is supported by the cover member 30 via the positive electrode resin member 70. In addition, in the present embodiment, the positive terminal member 50 is made of aluminum. However, the material of the positive terminal member 50 can be appropriately set within the range that it can be electrically connected to the positive electrode collector 41r of the electrode body 40 described later.
[0051] The negative electrode terminal member 60 is fixed to the cover member 30 via the negative electrode resin member 80 in a state of being insulated from the cover member 30. Therefore, the negative electrode terminal member 60 is supported by the cover member 30 via the negative electrode resin member 80. In the present embodiment, the negative electrode terminal member 60 is made of copper. However, the material of the negative electrode terminal member 60 can be appropriately set within the range that it can be electrically connected to the negative electrode collector 42r of the electrode body 40 described later.
[0052] The electrode body 40 is a so-called "wound type" electrode body. In the electrode body 40, a strip-shaped positive electrode plate 41 and a strip-shaped negative electrode plate 42 are wound in a predetermined winding direction with a strip-shaped separator (separator) 43 sandwiched therebetween. As a result, the electrode body 40 is formed as a whole into a flat shape having horizontally long rectangular sides extending in the vertical direction Z and the horizontal direction X on the front side F and the rear side B.
[0053] The positive electrode plate 41 has a positive electrode collector foil (not shown) and a positive electrode active material layer (not shown) carried on the collector foil. The collector foil of the positive electrode in the present embodiment is made of aluminum. Among them, the material of the positive electrode collector foil can be appropriately set within the range that can realize the function as the positive electrode of the lithium ion secondary battery. On the other hand, the negative electrode plate 42 has a negative electrode collector foil (not shown) and a negative electrode active material layer (not shown) carried on the collector foil. The collector foil of the negative electrode in the present embodiment is made of copper. Among them, the material of the negative electrode collector foil can be appropriately set within the range that can realize the function as the negative electrode of the lithium ion secondary battery.
[0054] In addition, a positive electrode collector portion 41r is formed in the electrode body 40. The positive electrode collector portion 41r is a portion where the collector foil of the positive electrode is exposed. The positive terminal lower side portion 52 of the positive terminal member 50 is bonded to the positive electrode collector portion 41r. Similarly, a negative electrode collector portion 42r is formed in the electrode body 40. The negative electrode collector portion 42r is a portion where the collector foil of the negative electrode is exposed. The negative terminal lower side portion 62 of the negative terminal member 60 is bonded to the negative electrode collector portion 42r. Therefore, the electrode body 40 is supported by the cover member 30 via the positive terminal member 50 and the negative terminal member 60.
[0055] Although detailed illustration is omitted, the positive electrode current collecting portion 41r is a portion protruding from the negative electrode plate 42 and the separator 43 in the axial direction of the electrode body 40, and only the positive electrode current collecting foil is wound. Similarly, the negative electrode current collecting portion 42r is a portion protruding from the positive electrode plate 41 and the separator 43 in the axial direction of the electrode body 40, and only the negative electrode current collecting foil is wound. In the present embodiment, the positive electrode current collecting portion 41r is formed at the end of the left side L of the electrode body 40. In addition, the negative electrode current collecting portion 42r is formed at the end of the right side R of the electrode body 40.
[0056] In addition, the electrode body 40 is at a certain distance from the bottom 12, the front side 13, the rear side 14, the left side 15 and the right side 16 of the main body member 20 and the cover member 30. In addition, an insulating support 5 for reliably maintaining insulation is arranged between the electrode body 40 and the main body member 20. As for the shape and material of the insulating support 5, as long as it can be arranged between the electrode body 40 and the main body member 20 and the electrode body 40 can be insulated from the main body member 20, it can be appropriately set. In the present embodiment, the insulating support 5 is composed of a strip film of polypropylene (PP) as a synthetic resin. In addition, the insulating support 5 is formed in a bag shape. Moreover, the bag-shaped insulating support 5 wraps the electrode body 40 in a state where the upper side U is open. That is, the insulating support 5 insulates the inner surface (inner surface) of the bottom 12, the front side 13, the rear side 14, the left side 15 and the right side 16 of the main body member 20 and the outer surface (outer surface) of the electrode body 40 opposite to the main body member 20.
[0057] The positive electrode resin member 70 is made of a thermoplastic resin, specifically polyphenylene sulfide (PPS). Moreover, the positive electrode resin member 70 is joined to the cover member 30 and the positive terminal member 50, respectively. By joining the positive electrode resin member 70 to the cover member 30 and the positive terminal member 50, the cover member 30, the positive terminal member 50 and the positive electrode resin member 70 are integrated, so the battery 1 including the integrated product constitutes a composite of metal and resin. In addition, the positive electrode resin member 70 insulates the cover member 30 from the positive terminal member 50 and seals it airtightly. That is, the positive electrode resin member 70 functions as an insulating member and a sealing member between the cover member 30 and the positive terminal member 50. Furthermore, as for the material of the positive electrode resin component 70, as long as it can insulate the cover component 30 and the positive terminal component 50 and seal it airtightly, and can be joined to the cover component 30 and the positive terminal component 50 respectively, it can be appropriately set and can be other types of resins such as other types of thermoplastic resins, thermosetting resins, etc.
[0058] The negative electrode resin member 80 is made of a thermoplastic resin, specifically polyphenylene sulfide (PPS). Moreover, the negative electrode resin member 80 is joined to the cover member 30 and the negative terminal member 60, respectively. By joining the negative electrode resin member 80 to the cover member 30 and the negative terminal member 60, the cover member 30, the negative terminal member 60 and the negative electrode resin member 80 are integrated, so the battery 1 including the integrated product constitutes a composite of metal and resin. In addition, the negative electrode resin member 80 insulates the cover member 30 and the negative terminal member 60 while sealing it airtightly. That is, the negative electrode resin member 80 functions as an insulating member and a sealing member between the cover member 30 and the negative terminal member 60. Furthermore, the material of the negative electrode resin member 80 can be appropriately set as long as it can insulate the cover member 30 and the negative terminal member 60 and seal them airtightly, and can be joined to the cover member 30 and the negative terminal member 60 respectively. It can be other types of resins such as other types of thermoplastic resins, thermosetting resins, etc.
[0059] Next, the shape of the positive electrode terminal member 50 will be described. Figure 3 is a three-dimensional diagram of the positive terminal component 50. Figure 3 As shown, the positive terminal member 50 includes a positive terminal upper portion 51, a positive terminal lower portion 52, and a positive terminal intermediate portion 53. In the battery 1, the positive terminal upper portion 51 is relatively arranged on the upper side U, and the positive terminal lower portion 52 is relatively arranged on the lower side D.
[0060] The positive terminal upper side portion 51 has a constant L-shaped cross-sectional shape in one direction. As a detail of the cross-sectional shape of the positive terminal upper side portion 51, compared with one straight line portion of the L-shaped, the other straight line portion is longer. Therefore, the rectangular plate-shaped portion of the positive terminal upper side portion 51 corresponding to the longer straight line portion of the L-shaped cross-sectional shape is referred to as the "long straight line portion 51a", and the portion extending vertically from one edge of the long straight line portion 51a is referred to as the "short straight line portion 51b".
[0061] In the following description of the positive terminal member 50, for convenience, the reference numerals for defining directions are used. Figure 3The reference numerals O, P, and Q are shown. The reference numerals O, P, and Q represent “the direction in which the L-shaped cross-sectional shape of the upper side portion 51 of the positive terminal extends constantly”, “the direction along the long straight line portion 51a of the L-shaped cross-sectional shape of the upper side portion 51 of the positive terminal”, and “the direction along the short straight line portion 51b of the L-shaped cross-sectional shape of the upper side portion 51 of the positive terminal”, respectively. In addition, the reference numerals O, P, and Q representing directions are hereinafter referred to as “the first direction O”, “the second direction P”, and “the third direction Q”, respectively. Furthermore, in the description of the positive terminal member 50, the side on the third direction Q where the upper side portion 51 of the positive terminal is arranged is sometimes referred to as the “upper side”, and the side on the third direction Q where the lower side portion 52 of the positive terminal is arranged is sometimes referred to as the “lower side”.
[0062] The lower side portion 52 of the positive terminal is formed vertically on the long straight portion 51a as a whole. The shape of the lower side portion 52 of the positive terminal is a rectangular plate with the third direction Q as the long side direction and the second direction P as the short side direction. In addition, in the first direction O, a part of the lower side portion 52 of the positive terminal is gathered inside the upper side portion 51 of the positive terminal, and the other part overflows to the outside of the upper side portion 51 of the positive terminal. Furthermore, in the second direction P, a part of the lower side portion 52 of the positive terminal is gathered inside the upper side portion 51 of the positive terminal, and the other part overflows to the outside of the upper side portion 51 of the positive terminal.
[0063] The positive terminal middle portion 53 is crank-shaped as a whole, connecting the positive terminal upper side portion 51 and the positive terminal lower side portion 52. The shape of the positive terminal middle portion 53 viewed from the second direction P is a rectangle with the first direction O as the long side direction and the third direction Q as the short side direction. In addition, the length of the first direction O of the positive terminal middle portion 53 is longer than the length of the first direction O of the positive terminal lower side portion 52. Moreover, the side surface of the positive terminal lower side portion 52 on one side exposed to the outside of the positive terminal upper side portion 51 in the first direction O is continuous with the side surface of the positive terminal middle portion 53 on the same side in the first direction O.
[0064] In addition, the two surfaces of the positive terminal middle portion 53 that are perpendicular to the second direction P near the connection with the short straight portion 51b and the two surfaces of the short straight portion 51b that are perpendicular to the second direction P are formed on the same plane. Hereinafter, the portion of the positive terminal middle portion 53 that is formed on the same plane with the two surfaces of the short straight portion 51b that are perpendicular to the second direction P is referred to as the "upper connecting portion 53a". Moreover, the surface 51x on the side of the positive terminal upper side portion 51 including the short straight portion 51b in the second direction P where the positive terminal lower side portion 52 is arranged is in the same plane as the surface 53ax on the same side of the upper connecting portion 53a. In addition, a curved portion 53b that is curved in a crank shape along the second direction P toward the outside of the positive terminal upper side portion 51 is formed on the opposite side of the short straight portion 51b in the third direction Q of the upper connecting portion 53a.
[0065] In the present embodiment, the shape of the negative terminal member 60 is the same as that of the positive terminal member 50. Therefore, the description using the perspective view of the negative terminal member 60 is omitted, and the negative terminal member 60 has a negative terminal upper side portion 61, a negative terminal lower side portion 62, and a negative terminal middle portion 63 corresponding to the positive terminal upper side portion 51, the positive terminal lower side portion 52, and the positive terminal middle portion 53, similarly to the positive terminal member 50.
[0066] Next, the bonding structure of the positive electrode resin member 70 , the cover member 30 , and the positive electrode terminal member 50 , and the roughening treatment of the cover member 30 and the positive electrode terminal member 50 will be described. Figure 4 To constitute Figure 1 and Figure 2 The figure shows a partial unit member 1A of the battery 1 extracted and shown in a perspective view, wherein the unit member 1A is composed of a cover member 30, a positive electrode terminal member 50 and a positive electrode resin member 70, a negative electrode terminal member 60 and a negative electrode resin member 80 which are integrated. Figure 5A for Figure 4 BB cross-section diagram, Figure 5B for Figure 4 CC cross-section diagram. Fig. 6A , 6B It is an explanatory diagram for explaining the bonding region between the cover member 30 and the positive electrode resin member 70 and the region of the cover member 30 subjected to the roughening treatment. Fig. 7A , 7B It is an explanatory diagram for explaining the joining region between the positive electrode terminal member 50 and the positive electrode resin member 70 and the region of the positive electrode terminal member 50 subjected to the roughening treatment.
[0067] The positive electrode terminal member 50 is fixed to the cover member 30 via the positive electrode resin member 70 in a state where the first direction O is parallel to the left-right direction X and the positive electrode terminal lower side portion 52 is arranged on the rear side B. On the other hand, the negative electrode terminal member 60 is fixed to the cover member 30 via the negative electrode resin member 80 in a state where the first direction O is parallel to the left-right direction X and the negative electrode terminal lower side portion 62 is arranged on the front side F.
[0068] The upper surface 51ax of the long straight portion 51a is exposed relative to the upper side U. In addition, in the up-down direction Z, the upper surface 30x of the cover member 30 and the lower surface 51ay of the long straight portion 51a are arranged at approximately the same position. Furthermore, in the up-down direction Z, the lower surface 51by of the short straight portion 51b is arranged at a position slightly lower than the lower surface 30y of the cover member 30. Furthermore, when viewed from above (from the upper side U to the lower side D), the long straight portion 51a of the positive terminal member 50 inserted into the positive electrode insertion hole 33h is completely accommodated inside the positive electrode insertion hole 33h. Moreover, in the left-right direction X and the front-back direction Y, the long straight portion 51a is arranged at approximately the center of the positive electrode insertion hole 33h.
[0069] The positive electrode resin member 70 is formed from the upper end of the positive terminal upper side portion 51 to the upper side U slightly higher than the lower end of the upper connecting portion 53a in the vertical direction Z. Moreover, the positive electrode resin member 70 is used to seal the lid member 30 and the positive electrode terminal member 50 in an airtight manner. In addition, as described later, in the present embodiment, the positive electrode resin member 70 is integrally formed by insert molding, and for convenience, the portion of the positive electrode resin member 70 on the upper surface 30x of the lid member 30 is referred to as the "positive electrode resin upper side portion 71", the portion under the lower surface 30y of the lid member 30 is referred to as the "positive electrode resin lower side portion 72", and the portion between the upper surface 30x and the lower surface 30y of the lid member 30, in other words, the portion filled in the positive electrode insertion hole 33h is referred to as the "positive electrode resin middle portion 73".
[0070] The positive electrode resin upper portion 71 includes a positive electrode resin upper frame portion 71 a surrounding the long straight portion 51 a over the entire circumference, and a positive electrode resin upper protrusion 71 b connected to the positive electrode resin upper frame portion 71 a .
[0071] The positive electrode resin upper frame-shaped portion 71a is formed into a rectangular frame shape when viewed from above. The distance from the inner edge to the outer edge of each straight line portion of the positive electrode resin upper frame-shaped portion 71a, i.e., the first width W1, is approximately the same. The positive electrode resin upper protrusion 71b is formed to protrude toward the right side R from a part of the range of the approximate center of the straight line portion formed on the right side R of the positive electrode resin upper frame-shaped portion 71a. The shape of the positive electrode resin upper protrusion 71b is a rectangular plate with the left-right direction X as the long side direction and the front-to-back direction Y as the short side direction. The length of the positive electrode resin upper protrusion 71b in the left-right direction X and the length in the front-to-back direction Y are longer than the first width W1. Furthermore, the positive electrode resin upper protrusion 71b is provided with a gate member GT (refer to Fig.12 ) part.
[0072] In addition, the positive electrode resin upper frame-shaped portion 71a is joined to the entire outer side surface of the long straight portion 51a and the rectangular ring-shaped cover upper surface frame-shaped joining area E11 that surrounds the edge of the positive electrode insertion hole 33h on the upper surface 30x of the cover member 30. The distance from the inner edge to the outer edge of each straight portion of the cover upper surface frame-shaped joining area E11, that is, the second width W2 is substantially the same. In addition, the positive electrode resin upper side protrusion 71b is joined to the upper surface of the cover member 30 over the entire range of the bottom surface.
[0073] In addition, the area of the upper surface 30x of the cover member 30 that is bonded to the positive electrode resin upper side protrusion 71b is hereinafter referred to as the "cover upper surface rectangular bonding area E12". The cover upper surface rectangular bonding area E12 is formed to protrude to the right side R from a part of the range of the approximate center of the straight line portion of the right side R in the cover upper surface frame-shaped bonding area E11. That is, the cover upper surface frame-shaped bonding area E11 and the cover upper surface rectangular bonding area E12 are connected to constitute the bonding area of the upper surface 30x of the cover member 30 with the positive electrode resin member 70. Therefore, the cover upper surface frame-shaped bonding area E11 and the cover upper surface rectangular bonding area E12 are collectively referred to as the "cover upper surface bonding area E1".
[0074] The positive electrode resin lower side portion 72 is formed as a whole in a rectangular plate shape with the left-right direction X as the long side direction and the front-rear direction Y as the short side direction. Inside the positive electrode resin lower side portion 72, the portion of the positive electrode terminal member 50 that overlaps with the positive electrode resin lower side portion 72 in the vertical direction Z is completely buried. Therefore, the positive electrode resin lower side portion 72 is joined to the entire outer side surface of the portion of the positive terminal member 50 that overlaps with the short straight line portion 51b and the upper connecting portion 53a in the vertical direction Z.
[0075] In addition, the positive electrode resin lower side portion 72 is bonded to the rectangular ring-shaped cover lower surface bonding area E2 that surrounds the edge of the positive electrode insertion hole 33h in the lower surface 30y of the cover member 30 over the entire circumference. The distance from the inner edge to the outer edge of each straight line portion of the cover lower surface bonding area E2 is substantially the same on the front side F and the rear side B, and substantially the same on the left side L and the right side R. Moreover, the fourth width W4, which is the distance from the inner edge to the outer edge of the straight line portion of the front side F and the rear side B, is wider than the third width W3, which is the distance from the inner edge to the outer edge of the straight line portion of the left side L and the right side R.
[0076] The positive electrode resin middle portion 73 is connected to the positive electrode resin upper portion 71 and the positive electrode resin lower portion 72. In addition, the positive electrode resin middle portion 73 is filled in the positive electrode insertion hole 33h. Therefore, the positive electrode resin middle portion 73 is joined to the inner side surface of the positive electrode insertion hole 33h of the cover member 30 over the entire circumference. Furthermore, inside the positive electrode resin middle portion 73, the portion of the short straight portion 51b of the positive terminal member 50 that overlaps with the positive electrode resin middle portion 73 in the vertical direction Z is completely buried. Therefore, the positive electrode resin middle portion 73 is joined to the entire outer side surface of the portion of the short straight portion 51b of the positive terminal member 50 that overlaps in the vertical direction Z.
[0077] Furthermore, the outer side surface of the long straight portion 51a of the positive terminal member 50 is entirely joined to the positive electrode resin upper frame-shaped portion 71a. In addition, in the positive terminal member 50, the outer side surface of the portion of the short straight portion 51b that overlaps with the positive electrode resin middle portion 73 and the positive electrode resin lower portion 72 in the up-down direction Z is entirely joined to the positive electrode resin middle portion 73 and the positive electrode resin lower portion 72. Furthermore, the outer side surface of the portion of the upper connecting portion 53a of the positive terminal member 50 that overlaps with the positive electrode resin lower portion 72 in the up-down direction Z is entirely joined to the positive electrode resin lower portion 72. Therefore, the area of the side surface of the positive terminal member 50 that crosses the positive terminal upper portion 51 and the upper connecting portion 53a to form the same plane and is joined to the positive electrode resin member 70 is referred to as the "terminal side joining area E3" (refer to Fig. 7A ). In addition, the entire lower surface 51ay of the long straight portion 51a on one side of the positive terminal lower side portion 52 formed in the third direction Q of the positive terminal member 50, that is, the area joined to the positive electrode resin member 70 is referred to as the "terminal lower side joining area E4" (refer to Figure 7B ).
[0078] Thus, there are a plurality of bonding regions with the positive electrode resin member 70 in the cover member 30 and the positive electrode terminal member 50. In order to improve the sealing performance, a roughening treatment using pulsed laser irradiation is performed on specific regions of the cover member 30 and the positive electrode terminal member 50 including the bonding regions with the positive electrode resin member 70. Therefore, the roughening treatment is described.
[0079] The roughening treatment is applied to the cover upper surface roughened area F1 which completely surrounds and receives the cover upper surface bonding area E1 in the upper surface 30x of the cover member 30 and the cover lower surface roughened area F2 which completely surrounds and receives the cover lower surface bonding area E2 in the lower surface 30y of the cover member 30. In addition, the roughening treatment is applied to the terminal side surface roughened area F3 which completely surrounds and receives the terminal side surface bonding area E3 in the entire side surface of the positive terminal member 50 which crosses the positive terminal upper side portion 51 and the upper connecting portion 53a and forms the same plane, and the terminal lower surface bonding area E4 itself, that is, the terminal lower surface roughened area F4.
[0080] The detailed conditions will be described later. The roughening treatment of the cover upper surface roughening area F1, the cover lower surface roughening area F2, the terminal side roughening area F3 and the terminal lower surface roughening area F4 is performed by pulse laser irradiation. Then, the base layer 35 formed by stacking the fragmented particles in the cover upper surface roughening area F1 and the cover lower surface roughening area F2, and the column group layer 36 in which a large number of nano columnar bodies 361 extending in the height direction and stacking the fragmented particles in a rosary-like manner are two-dimensionally arranged. Similarly, the base layer 55 formed by stacking the fragmented particles in the terminal side roughening area F3 and the terminal lower surface roughening area F4, and the column group layer 56 in which a large number of nano columnar bodies 561 extending in the height direction and stacking the fragmented particles in a rosary-like manner are two-dimensionally arranged. That is, the upper surface joining area E1 and the lower surface joining area E2 of the cover, which are joined to the positive electrode resin component 70 and seal the outer side and the inner side (the first space and the second space) of the battery 1 together with the positive electrode resin component 70, include: a base layer 35 formed by surface-debris particles accumulated on the surface of the cover component 30 in a planar shape, and a column group layer 36 in which nano-columnar bodies 361 are two-dimensionally arranged and connected in a rosary-like manner and extend in the height direction from the base layer 35, and the fragment particles are connected. Similarly, the terminal side joining area E3 and the terminal bottom joining area E4, which are joined to the positive electrode resin component 70 and seal the outer side and the inner side (the first space and the second space) of the battery 1 together with the positive electrode resin component 70, include: a base layer 55 formed by surface fragment particles accumulated in a planar shape on the surface of the positive terminal component 50, and a terminal side roughening area F3 and a terminal bottom surface roughening area F4 of a column group layer 56 in which nano-columnar bodies 561 are two-dimensionally arranged and connected in a rosary-like manner and extend from the base layer 55 in the height direction.
[0081] Furthermore, the so-called fragment particles refer to particles with a diameter of less than 100 nm that are formed by condensation of compounds formed by the reaction of metal vapor or metal atoms with atmospheric gas when a part of the surface is explosively evaporated by irradiating the surface of a metal component with a pulsed laser, and fall onto the surface near the laser irradiation position.
[0082] The average height of a large number of nano-columns 361 standing as column group layers 36 in each of the cover upper surface roughening region F1 and the cover lower surface roughening region F2, and the average height of a large number of nano-columns 561 standing as column group layers 56 in each of the terminal side roughening region F3 and the terminal lower surface roughening region F4 are greater than 84nm and less than 1000nm.
[0083] In addition, the average surface area ratio of the cover upper surface roughened region F1, the cover lower surface roughened region F2, the terminal side roughened region F3, and the terminal lower surface roughened region F4 is greater than 12.9. The surface area ratio here refers to the value obtained by dividing the true surface area (true surface area) of each roughened region F1 to F4 plus the concavities and convexities including the nanocolumnar bodies 361 and 561 by the geometric surface area of each roughened region F1 to F4.
[0084] Here, an image showing how the metal member (cover member 30, positive electrode terminal member 50) is actually roughened by pulse laser irradiation to form a foundation layer (foundation layer 35, 55) and a column group layer (column group layer 36, 56) is shown. Figure 8 .like Figure 8 As shown, a base layer (base layer 35, 55) formed by the accumulation of fragment particles is stacked on the surface of the metal component (cover component 30, positive terminal component 50). Furthermore, a column group layer (column group layer 36, 56) in which a large number of nano columns (nano columns 361, 561) are connected in a rosary-like manner and extend in the height direction and are two-dimensionally arranged is stacked on the base layer (base layer 35, 55). It should be noted that in Figure 8 The interval of the scale written on the lower right corner of the image represents 30 nm per one portion.
[0085] In the battery 1, the resin (polyphenylene sulfide) of the positive electrode resin member 70 is filled in the gaps between the nano-columnar bodies 361 and 561 until it reaches the base layers 35 and 55. In other words, the positive electrode resin member 70 is bonded to the surface of each nano-columnar body 361 and 561 and the surface of the base layers 35 and 55. Here, an image showing the state in which the resin (polyphenylene sulfide) of the positive electrode resin member 70 is actually filled in the gaps between a large number of nano-columnar bodies (nano-columnar bodies 361 and 561) is shown. Fig.9A , 9B It should be noted that Fig.9A The interval of the scale written on the lower right corner of the image (left side) represents 10 μm per unit, and the interval of the scale written on the lower right corner of FIG. B9 (right side image) represents 15 nm per unit.
[0086] It should be noted that the bonding structure and use of the negative electrode resin member 80, the cover member 30 and the negative electrode terminal member 60 Figures 5A to 9B The above-described positive electrode resin member 70 is configured similarly to the joint structure of the cover member 30 and the positive electrode terminal member 50. In addition, the joint area between the cover member 30 and the negative electrode resin member 80 and the joint area between the negative electrode terminal member 60 and the negative electrode resin member 80 are roughened and used. Figures 5A to 9B The above-described roughening treatments for the lid member 30 and the positive electrode terminal member 50 are configured similarly.
[0087] [Battery Manufacturing]
[0088] Next, regarding the method for manufacturing the battery 1, refer to Fig.10 The manufacturing method of the battery 1 includes a component preparation step S1, a laser irradiation step S2, an insert molding step S3, a cap assembly completion step S4, a closing step S5, a welding step S6, a liquid injection and sealing step S7, and an initial charge and aging step S8.
[0089] In the component preparation step S1, the cover member 30, the positive electrode terminal member 50, and the negative electrode terminal member 60 are prepared. Specifically, the liquid injection hole 30k, the positive electrode insertion hole 33h, the negative electrode insertion hole 34h, and the safety valve 19 are formed on the aluminum plate by using a conventional general processing method, thereby obtaining the cover member 30. In addition, the positive electrode terminal member 50, and the negative electrode terminal member 60 are obtained from the aluminum plate by using a conventional general processing method. Figure 3 A positive electrode terminal member 50 of the shape shown is obtained. Furthermore, a negative electrode terminal member 60 of the same shape as the positive electrode terminal member 50 is obtained from a copper plate by a conventional general processing method.
[0090] After the component preparation step S1, the laser irradiation step S2 is performed. In the laser irradiation step S2, the surface of the cover member 30, which can become the cover upper surface roughening area F1 and the cover lower surface roughening area F2 in a state where the base layer 35 and the column group layer 36 are not formed, is subjected to a roughening treatment using pulsed laser irradiation, so that the fragmented particles from the cover member 30 are accumulated and grown into a large number of nano-columnar bodies 361, forming the cover upper surface roughening area F1 and the cover lower surface roughening area F2. Similarly, in the laser irradiation step S2, the surface of the positive terminal member 50, which can become the terminal side roughening area F3 and the terminal lower surface roughening area F4 in a state where the base layer 55 and the column group layer 56 are not formed, is subjected to a roughening treatment using pulsed laser irradiation, so that the fragmented particles from the positive terminal member 50 are accumulated and grown into a large number of nano-columnar bodies 561, forming the terminal side roughening area F3 and the terminal lower surface roughening area F4.
[0091] As an example of various conditions for pulse laser irradiation in the laser irradiation step S2, the energy density of one pulse of laser irradiation is set to 24 J / cm in the case of aluminum. 2 In the case of copper, it becomes 32 J / cm 2 . And, for example, for aluminum, the wavelength is set to 1060 nm, the average output power is set to 25 W, the pulse period is set to 40 μs, the pulse width is set to 50 ns, the spot diameter is set to 63 μm, the conveying speed is set to 1450 mm / s, and the line spacing is set to 0.059 mm. Fig.11A , 11B The figure schematically shows the trajectory of pulse laser irradiation when the pulse laser irradiation is performed on the cover lower surface roughened region F2 and the terminal side surface roughened region F3 in the laser irradiation step S2.
[0092] like Fig.11A As shown, for the cover lower surface roughened region F2, on one side along the left-right direction X in the cover lower surface roughened region F2 ( Fig.11A The top of the left side L) ( Fig.11A , recorded as the "starting point" side), proceed to one side in the forward and backward direction Y ( Fig.11A Then, the pulse laser is irradiated to the other side ( Fig.11A The right side R in the middle is offset from the set line spacing (0.059mm) and the other side ( Fig.11A Then, the pulse laser is irradiated to the other side ( Fig.11A The right side R in the middle is offset from the set line spacing (0.059mm), and one side in the forward and backward direction Y is again ( Fig.11A After that, the pulsed laser irradiation is repeated until the pulsed laser irradiation traveling to one side or the other side in the front-rear direction Y reaches the other side ( Fig.11A The top of the right side R) ( Fig.11A The side recorded as the “end point” in FIG.
[0093] By irradiating the roughened area F2 under the cover with pulsed laser in this way, a base layer 35 and a column group layer 36 are formed. Initially, the fragmented particles of the cover member 30 are attached to the surface of the cover member 30 in a scattered manner, and the base layer 35 is formed in a planar shape. Next, if the scattered attachment of the fragmented particles proceeds, the fragmented particles are combined with the base layer 35, and a large number of short protruding nano-columnar bodies 361 extending in the height direction stand two-dimensionally. Then, if the scattered attachment of the fragmented particles proceeds further, the fragmented particles are combined with the base layer 35 in a rosary-like manner, and a large number of long columnar nano-columnar bodies 361 extending in the height direction stand two-dimensionally. Furthermore, for example, by increasing the energy density of the pulsed laser irradiation, nano-columnar bodies 361 with a high average height can be formed.
[0094] In addition, the position where the pulse laser irradiation starts in the cover lower surface roughening area F2 ( Fig.11A The side described as "starting point" in the text is not limited to Fig.11A , Fig.11A The side described as the "end point" in the figure may also be the position where the pulse laser irradiation starts. In addition, the pulse laser irradiation of the roughened surface area F1 on the cover is also the same as Fig.11A The pulse laser irradiation on the cover lower surface roughened region F2 shown in the figure is performed in the same manner. However, the pulse laser irradiation on the cover upper surface roughened region F1 and the pulse laser irradiation on the cover lower surface roughened region F2 may be performed in different manners.
[0095] like Fig. 11B As shown, for the terminal side roughened region F3, at the top end ( Fig. 11B Next, the positive terminal member 50 along the third direction Q is shifted by a set line spacing (0.059 mm) to the other side, and pulsed laser irradiation is performed in the other direction O. Then, the positive terminal member 50 along the third direction Q is shifted by a set line spacing (0.059 mm) to the other side, and pulsed laser irradiation is performed in the other direction O. Then, the positive terminal member 50 along the third direction Q is shifted by a set line spacing (0.059 mm) to the other side, and pulsed laser irradiation is performed again in the first direction O. Thereafter, the pulsed laser irradiation is repeated until the pulsed laser irradiation in one direction or the other direction in the first direction O reaches the top of the other side of the terminal side roughening area F3 along the third direction Q ( Fig. 11B The side recorded as the “end point” in FIG.
[0096] By irradiating the roughened area F3 on the side of the terminal with pulsed laser in this way, a base layer 55 and a column group layer 56 are formed. Initially, the fragmented particles of the positive terminal member 50 are attached to the surface of the positive terminal member 50 in a scattered manner, forming a base layer 55 in a planar shape. Next, if the scattered attachment of the fragmented particles proceeds, the fragmented particles are combined with the base layer 55, and a large number of short protruding nano-columnar bodies 561 extending in the height direction are two-dimensionally arranged. Then, if the scattered attachment of the fragmented particles proceeds further, the fragmented particles are combined with the base layer 55 in a rosary-like manner, and a large number of long columnar nano-columnar bodies 561 extending in the height direction are two-dimensionally arranged. Furthermore, for example, by increasing the energy density of pulsed laser irradiation, nano-columnar bodies 561 with a high average height can be formed.
[0097] In addition, the position where the pulse laser irradiation starts in the terminal side roughening area F3 ( Fig. 11B The side described as "starting point" in the text is not limited to Fig. 11B , Fig. 11B The side recorded as the "end point" in the figure can also be the starting point of pulse laser irradiation. In addition, the pulse laser irradiation of the roughened area F4 on the lower surface of the terminal is also the same as Fig. 11B The pulse laser irradiation for the terminal side roughening area F3 shown in the figure is performed in the same manner. However, in this case, the direction of the pulse laser irradiation is the same as the laser irradiation for the terminal side roughening area F3, and the starting position and the ending position of the pulse laser irradiation become the top of one side and the top of the other side of the terminal lower surface roughening area F4 along the first direction O of the positive terminal member 50. Furthermore, the direction of the pulse laser irradiation is shifted by the set line spacing (0.059 mm) to become one of the second directions P of the positive terminal member 50.
[0098] In the laser irradiation step S2, the bonding area around the negative electrode insertion hole 34h of the cover member 30 and the negative electrode resin member 80 is subjected to pulse laser irradiation in a manner substantially similar to the case of the cover upper surface roughened area F1 and the cover lower surface roughened area F2. Similarly, the bonding area between the negative electrode terminal member 60 and the negative electrode resin member 80 is subjected to pulse laser irradiation in a manner substantially similar to the case of the terminal side surface roughened area F3 and the terminal lower surface roughened area F4. The "substantially the same manner" here refers to the area subjected to pulse laser irradiation and the conditions of pulse laser irradiation.
[0099] After the laser irradiation step S2, an insert molding step S3 is performed. In the insert molding step S3, the positive electrode resin member 70 and the negative electrode resin member 80 are formed, and the positive electrode resin member 70 is joined to the cover member 30 and the positive electrode terminal member 50 to form an integrated body, and the negative electrode resin member 80 is joined to the cover member 30 and the negative electrode terminal member 60 to form an integrated body. That is, the unit member 1A as a metal-resin composite is manufactured. Fig.12 It is an explanatory diagram schematically showing the insert molding step S3 on the positive electrode terminal member 50 side.
[0100] In the insert molding step S3, a mold DE is used. The mold DE has a lower mold DE1 arranged on the lower side and an upper mold DE2 arranged on the upper side. Initially, by setting the lower mold DE1 and the upper mold DE2, the cover member 30, the positive terminal member 50 and the negative terminal member 60 are arranged at a predetermined position. At this time, the positive terminal member 50 inserted into the positive electrode insertion hole 33h, the negative terminal member 60 inserted into the negative electrode insertion hole 34h and the cover member 30 are supported integrally by the mold DE. In addition, the space CV corresponding to the positive electrode resin member 70 and the negative electrode resin member 80 is formed by the set lower mold DE1 and the upper mold DE2.
[0101] In the insert molding process S3, the filling process S31 is first performed, and then the curing process S32 is performed. In the filling process S31, as shown in FIG. Fig.12 As shown, the molten resin MR, which will become the material of the positive electrode resin member 70 and the negative electrode resin member 80, is injected from the gate member GT through the upper mold DE2 into the space CV formed by the lower mold DE1 and the upper mold DE2. At this time, for example, the molten resin MR fills the gaps between the large number of nano-columnar bodies 361 forming the column group layer 36 until it reaches the base layer 35. Similarly, the molten resin MR fills the gaps between the large number of nano-columnar bodies 561 forming the column group layer 56 until it reaches the base layer 55.
[0102] The material of the positive electrode resin member 70 and the negative electrode resin member 80 contains polyphenylene sulfide as a main component, and the material of the positive electrode resin member 70 and the negative electrode resin member 80 contains a glass filler. The linear expansion coefficient of the material of the positive electrode resin member 70 and the negative electrode resin member 80 is set between the linear expansion coefficient of copper (1.65) and the linear expansion coefficient of aluminum (2.31).
[0103] Then, after the molten resin MR is injected, as a solidification step S32, the molten resin MR is appropriately cooled to form the positive electrode resin member 70 and the negative electrode resin member 80. Specifically, for example, in the filling step S31, the molten resin MR that fills the gaps between the large number of nano columns 361 until it reaches the base layer 35, and the molten resin MR that fills the gaps between the large number of nano columns 561 until it reaches the base layer 55 is solidified to form the positive electrode resin member 70 joined to the joining areas E1 to E4 including the roughened areas F1 to F4. Similarly, the negative electrode resin member 80 is also formed. Then, the upper mold DE2 is moved upward, and the unit member 1A consisting of the integrated cover member 30, the positive electrode resin member 70 and the positive terminal member 50, the negative electrode resin member 80 and the negative terminal member 60 is taken out from the lower mold DE1.
[0104] Following the insert molding step S3, the cover assembly completion step S4 is performed. In the cover assembly completion step S4, the cover assembly is completed. Specifically, the electrode body 40 is prepared, and the lower side portion 52 of the positive terminal and the lower side portion 62 of the negative terminal of the unit member 1A generated by the insert molding step S3 are respectively welded to the positive electrode collector 41r and the negative electrode collector 42r of the electrode body 40. Then, the electrode body 40 in this state is wrapped with a bag-shaped insulating bracket 5. As a result, the cover assembly consisting of the cover member 30, the positive terminal member 50, the negative terminal member 60, the positive electrode resin member 70, the negative electrode resin member 80, the electrode body 40 and the insulating bracket 5 is completed.
[0105] After the cover assembly completion step S4, the closing step S5 is performed. In the closing step S5, the main member 20 is prepared, and the portion below the cover member 30 including the electrode body 40 and the insulating bracket 5 in the cover assembly completed in the cover assembly completion step S4 is inserted into the main member 20, and the opening 21 of the main member 20 is closed with the cover member 30.
[0106] Following the closing step S5, the welding step S6 is performed. In the welding step S6, the top ends of the upper sides U of the front side 13, the rear side 14, the left side 15, and the right side 16 of the main body member 20 in the vertical direction Z are laser welded to the peripheral edge of the cover member 30 over the entire circumference, thereby hermetically sealing the opening 21.
[0107] Following the welding step S6, the liquid injection and sealing step S7 is performed. In the liquid injection and sealing step S7, the electrolyte 3 is injected into the housing 10 through the liquid injection hole 30k, so that the electrolyte 3 is impregnated into the electrode body 40. Then, the sealing member 39 is inserted into the liquid injection hole 30k from the upper side U, and the sealing member 39 is welded to the cover member 30 around the entire circumference, so that the sealing member 39 and the cover member 30 are hermetically sealed.
[0108] After the liquid injection and sealing step S7, the charging and aging step S8 is performed. In the charging and aging step S8, a charging device (not shown) is connected to the battery 1 to perform initial charging on the battery 1. Then, the initially charged battery 1 is left for a predetermined time to perform aging on the battery 1. In this way, the battery 1 is completed.
[0109] Next, an experiment for verifying the sealing performance of the joint between the metal component and the resin component will be described. This experiment was conducted by the applicant. In addition, this experiment is referred to as a "sealing performance verification experiment". The sealing performance verification experiment consists of the following three steps (1) to (3).
[0110] (1) Preparation of test specimens
[0111] (2) Implementation of the liquid tank thermal shock test
[0112] (3) Implementation of helium leak test
[0113] First, (1) the preparation of the test specimen is described. The test specimen is a test object for the sealing property verification test. Fig.13A , 13B 1 is an explanatory diagram schematically showing a test specimen 100. Specifically, Fig.13A is a top view of the test specimen 100, Fig. 13B for Fig.13A DD cross-sectional view. The test specimen 100 is formed by joining a plate-shaped metal member 101 and a resin member 102. The plate-shaped metal member 101 is made of aluminum or copper. That is, as the test specimen 100, a plate-shaped metal member made of aluminum and a plate-shaped metal member made of copper are prepared. In addition, the resin member 102 is made of only polyphenylene sulfide (PPS).
[0114] The plate-like metal member 101 is formed in a square shape as a whole regardless of the type of the metal member. A vent hole 103 is formed in the center of the metal member in a plan view so as to penetrate the metal member 101 in the thickness direction.
[0115] A roughened area F101 is formed on the surface 101A of the side of the metal component 101 that is joined to the resin component 102. The shape of the roughened area F101 is an annular shape that surrounds the edge of the vent 103 with a substantially constant width. In the roughened area F101, as in the above-mentioned roughened areas F1 to F4, a base layer and a column group layer are stacked by pulsed laser irradiation. However, in the sealing verification experiment, a plurality of test specimens 100 are prepared, and each test specimen is subjected to pulsed laser irradiation under different conditions. Therefore, the average height and surface area ratio of the nanocolumnar bodies also vary depending on the test specimen. Fig.14TABLE 1 is a table showing the relationship between various conditions of pulsed laser irradiation on the roughened region F101 and the average height and surface area ratio of the nanocolumnar bodies formed in the roughened region F101. In the sealing performance verification experiment, seven metal members 101 made of aluminum and seven metal members 101 made of copper were prepared.
[0116] Then, insert molding is used to join the resin member 102 to each metal member 101. The shape of the resin member 102 is a circular plate. Moreover, the central axis of the resin member 102 is roughly consistent with the central axis of the vent 103. Therefore, in this experiment, the joining area E100 of the resin member 102 and the metal member 101 is consistent with the roughened area F101 of the metal member 101. In addition, the resin member 102 is joined to the roughened area F101 around the vent 103 all around in a state where the vent 103 is completely covered. That is, in this experiment, the joining portion between the resin member 102 and the metal member 101 will seal between the space (first space SPx) on the side of the metal member 101 that is joined to the resin member 102 and the space (second space SPy) on the side that is not joined to the resin member 102 of the metal member 101 constituting the test specimen 100.
[0117] Next, (2) the liquid tank thermal shock test will be described. The liquid tank thermal shock test was performed on each test specimen 100 using a conventional liquid tank thermal shock apparatus (ES-96EXH-LS, manufactured by Hitachi Appliances Ltd.).
[0118] Finally, (3) the helium leakage test will be described. A known helium leakage test was performed on each test specimen 100 that had undergone the liquid tank thermal shock test using a conventional helium leakage tester (HELiOT900, manufactured by Albuck Co., Ltd.).
[0119] The results of the helium leak test (3) are shown in Fig.15A , 15B . Fig.15A This is a scatter plot with the horizontal axis representing the average height of the nanocolumns and the vertical axis representing the helium leakage rate. Fig. 15B This is a scatter plot with the horizontal axis representing the surface area ratio and the vertical axis representing the helium leakage rate.
[0120] Fig.15A and Fig. 15B The vertical axis shows that the amount of helium leakage decreases as you go up. Fig.15A , 15B As shown in FIG. 1 , in the sealing verification experiment, if the average height of the nanocolumnar bodies is 84 nm or more or the surface area ratio is 12.9 or more, the sealing of the joint between the metal member 101 and the resin member 103 is good. Fig.15A ,15B The symbol "NG" indicates poor sealing.
[0121] Here, the calculation method of the average height of the nano-columnar bodies in each roughened area in the sealing verification experiment is described. As the calculation method, initially, a plate-shaped metal component is prepared as a test piece. The test piece of the metal component is called an "average height test piece". Then, a whole plane of each average height test piece is subjected to pulse laser irradiation under various conditions.
[0122] Next, a cross-sectional sample including a planar portion irradiated with pulsed laser light was prepared from each average height test piece using a predetermined cross-sectional sample preparation device (e.g., CrossSection Polyshair (registered trademark): manufactured by JEOL Ltd.). The cross-sectional sample was parallel to the thickness direction of the average height test piece. Next, a cross-sectional image of each cross-sectional sample was obtained using a scanning electron microscope (S-4800, Hitachi High-Technologies Co., Ltd.). It should be noted that the magnification of the cross-sectional image was 150,000 times.
[0123] Next, the cross-sectional area and bottom length of the nanocolumnar bodies in each cross-sectional image are measured using known image processing software. Then, the height of the nanocolumnar bodies is calculated according to the following mathematical formula 1.
[0124] (Formula 1)
[0125] Height of nanorod (nm) = cross-sectional area of nanorod (nm) 2 )÷base length (nm)
[0126] Fig.16A This is an example of a cross-sectional image obtained using a scanning electron microscope. Fig. 16B Based on Fig.16A A diagram illustrating the cross-sectional area CA and the bottom length BL of a nanocolumnar body. Fig. 16B As shown in FIG. 1 , the length of the curved portion is the bottom length BL, and the total area of the nanocolumns standing in a forest is the cross-sectional area CA of the nanocolumns. Fig.16A , Fig. 16B The interval of the scale written on the lower right corner of the image represents 30 nm per one portion.
[0127] Next, the calculation method of the surface area ratio of each roughened area in the sealing verification experiment is explained. As the calculation method, a plate-shaped metal component is first prepared as a test piece. The test piece of the metal component is called a "surface area ratio test piece". Then, a plane of each surface area ratio test piece is subjected to pulse laser irradiation under various conditions. In this experiment, the object of pulse laser irradiation is a plane. Next, the specific surface area of the surface area ratio test piece subjected to the pulse laser irradiation is determined by a general krypton gas adsorption method.
[0128] Next, based on the measured specific surface area of the surface area ratio test piece, the roughened surface area of the plane irradiated with the pulsed laser in the surface area ratio test piece was calculated. The roughened surface area was calculated according to the following mathematical formula 2.
[0129] (Formula 2)
[0130] Roughened surface area (m 2 ) = specific surface area (m 2 / g) × surface area ratio: total weight of the test piece (g) - surface area of the unroughened portion (m 2 )
[0131] Furthermore, based on the calculated roughened surface area of the test piece for surface area ratio, the surface area ratio of the plane irradiated with the pulsed laser in the test piece for surface area ratio is calculated. The surface area ratio is calculated according to the following mathematical formula 3.
[0132] (Formula 3)
[0133] Surface area ratio = roughened surface area (m 2 )÷geometric surface area (m 2 )
[0134] As described above, according to the cover member 30 having the joining areas E1 and E2, the surface of the member is joined to the positive electrode resin member 70 and together with the positive electrode resin member 70, it seals the first space (SP1) on the outside of the battery 1 and the second space (SP2) on the inside of the battery 1. The joining areas E1 and E2 are formed on the member surface of the cover member 30. The joining areas E1 and E2 include the roughened areas F1 and F2 of the column group layer 36 in which the base layer 35 is formed by the accumulation of fragment particles and the nano columns 361 extending in the height direction connected in a rosary-like manner. The average height of the nano columns 361 is greater than 84 nm. Therefore, compared with, for example, a metal member in which a protruding portion that cannot be said to be a columnar portion is formed, the sealing of the joining surface with the positive electrode resin member 70 can be improved. Similarly, according to the positive terminal component 50 having joining areas E3 and E4, the joining areas E3 and E4 are formed on the component surface of the positive terminal component 50, and the joining areas E3 and E4 include a base layer 55 formed by the accumulation of fragment particles, and nano-columns 561 extending in the height direction connected in a rosary-like manner to the fragment particles, and coarsened areas F3 and F4 of a column group layer 56 in which a two-dimensional forest is formed on the base layer 55. The average height of the forested nano-columns 561 is greater than 84 nm. Therefore, compared with, for example, a metal component in which a protrusion that cannot be said to be a columnar portion is formed, the sealing of the joining surface with the positive electrode resin component 70 can be improved.
[0135] In addition, the joining areas E1 and E2 are formed into an annular shape in a manner that surrounds the edge of the positive electrode insertion hole 33h all around, and the roughened areas F1 and F2 are formed into annular shapes corresponding to their shapes in the joining areas E1 and E2, so that the sealing of the positive electrode insertion hole 33h is improved when the joining areas E1 and E2 are joined to the positive electrode resin component 70.
[0136] Furthermore, the resin forming the positive electrode resin member 70 joined to the joining regions E1 and E2 is filled in the gaps between the nano columnar bodies 361 until it reaches the base layer 35, so the sealing of the joining portion between the cover member 30 and the positive electrode resin member 70 is improved. Similarly, the resin forming the positive electrode resin member 70 joined to the joining regions E3 and E4 is filled in the gaps between the nano columnar bodies 561 until it reaches the base layer 55, so the sealing of the joining surface between the positive terminal member 50 and the positive electrode resin member 70 is improved.
[0137] In addition, the manufacturing method of the cover member 30 as a metal member includes a laser irradiation step S2, wherein on the surface of the cover member 30 which can become the roughened area F1, F2 in a state where the base layer 35 and the column group layer 36 have not yet been formed, fragment particles of aluminum, which is a raw material of the cover member 30, are accumulated due to the irradiation of pulsed laser and grow into nano-columns 361 to form the roughened areas F1, F2. Therefore, a large number of nano-columns 361 with a size of 84 nm or more can be made to stand, and a cover member 30 with high sealing performance can be obtained. Similarly, the manufacturing method of the positive terminal component 50 includes a laser irradiation step S2, wherein the surface of the positive terminal component 50 which can become the roughened area F3, F4 in a state where the base layer 55 and the column group layer 56 have not yet been formed is caused to accumulate fragment particles of aluminum, which is the raw material of the positive terminal component 50, due to pulsed laser irradiation, and grow into nano-columns 561 to form the roughened areas F3, F4. Therefore, a large number of nano-columns 561 with a size of more than 84 nm can be made to stand, and a positive terminal component 50 with high sealing performance can be obtained.
[0138] Furthermore, a method for manufacturing a battery 1 as a metal-resin composite includes: a filling step S31, in which the material of the hot-melted positive electrode resin component 70, namely, the molten resin MR, is filled into the gaps between the large number of nano-columnar bodies 361 forming the column group layer 36 until it reaches the base layer 35, and at the same time, the gaps between the large number of nano-columnar bodies 561 forming the column group layer 56 are filled into the gaps between the large number of nano-columnar bodies 561 forming the column group layer 56 until it reaches the base layer 55; and a curing step S32, in which the molten resin MR filled into the gaps between the large number of nano-columnar bodies 361 forming the column group layer 36 in the filling step S31 and the molten resin MR filled into the gaps between the large number of nano-columnar bodies 561 forming the column group layer 56 are cured to form a positive electrode resin component 70 bonded to the roughened regions F1 to F4, so that the positive electrode resin component 70 is bonded to the surfaces of the base layers 35, 55 and the surfaces of the nano-columnar bodies 361, 561, so that a battery 1 with high sealing performance can be obtained.
[0139] In addition, as described above, the bonding region of the cover member 30 and the negative electrode resin member 80 is subjected to a roughening treatment similar to the roughening regions F1 and F2, and a large number of nanocolumns with an average height of 84 nm or more stand in a forest, so that the sealing performance of the bonding region of the cover member 30 and the negative electrode resin member 80 can also be improved. Furthermore, the bonding region of the negative electrode terminal member 60 and the negative electrode resin member 80 is subjected to a roughening treatment similar to the roughening regions F3 and F4, and a large number of nanocolumns with an average height of 84 nm or more stand in a forest, so that the sealing performance of the bonding region of the negative electrode terminal member 60 and the negative electrode resin member 80 can also be improved.
[0140] It should be noted that the present embodiment is merely an example and does not limit the present invention in any way. Therefore, the present invention can be modified and altered in various ways without departing from the gist of the present invention. The following describes the modified and altered examples of the present embodiment.
[0141] In this embodiment, a flat wound electrode body 40 is exemplified as the electrode body housed in the case 10, but the electrode body may also be a stacked electrode body. In addition, in this embodiment, one electrode body is housed in the case 10, but a plurality of electrode bodies may be housed in the case 10.
[0142] In the present embodiment, the shell 10 is a flat rectangular parallelepiped with a bottom as a whole, and the shape of the shell 10 can also be appropriately deformed and can be other shapes such as a cylinder. In addition, the shape of one or both of the positive terminal member 50 and the negative terminal member 60 can be appropriately deformed. Similarly, the shape of one or both of the positive electrode resin member 70 and the negative electrode resin member 80 can be appropriately deformed. Furthermore, in the present embodiment, the shape of the positive terminal member 50 can be the same as or different from the shape of the negative terminal member 60. Similarly, in the present embodiment, the shape of the positive electrode resin member 70 can be the same as or different from the shape of the negative electrode resin member 80.
[0143] In the present embodiment, the battery 1 in which the metal cover member 30 and the positive electrode terminal member 50 are each joined to the positive electrode resin member 70, and the metal cover member 30 and the negative electrode terminal member 60 are each joined to the negative electrode resin member 80 is included in the metal-resin composite of the present invention, and the unit member 1A constituting the battery 1 is also included in the metal-resin composite of the present invention.
[0144] In this embodiment, the present invention is applied to lithium-ion batteries, but it can be applied to any general power storage device, for example, the present invention can also be applied to nickel-hydrogen batteries and nickel-cadmium batteries. In addition, the use of the present invention is not limited to batteries, and can be widely applied to composites that connect metal components and resin components.
[0145] In this embodiment, the positive electrode resin component 70 reaches the base layer 35 of the roughened regions F1 and F2 and the base layer 55 of the roughened regions F3 and F4. For example, the molten resin MR forming the positive electrode resin component 70 can be filled in the gaps between a large number of nanocolumns 361 and a large number of nanocolumns 561 when it reaches the top of the nanocolumns 361 and 561 as a whole, the part between the top and the middle, the approximate middle, or the part between the middle and the base end.
[0146] In the present embodiment, the roughened regions F1 and F2 are formed in the entirety of the joining regions E1 and E2, but the roughened regions F1 and F2 may be formed in a portion of the joining regions E1 and E2. However, in this case, it is preferred that the roughened regions F1 and F2 are formed in the joining regions E1 and E2 in a ring shape in a manner that surrounds the positive electrode insertion hole 33h. In addition, the roughened regions F3 and F4 are formed in the entirety of the joining regions E3 and E4, but the roughened regions F3 and F4 may be formed in a portion of the joining regions E3 and E4. However, in this case, it is preferred that the roughened region F3 is formed as a whole in the portion of the middle portion 53 of the positive electrode terminal in the joining region E3. In addition, it is preferred that the roughened region F4 is formed in a ring shape along the peripheral portion of the joining region E4.
Claims
1. A metal member having a bonding area on its surface, the bonding area being bonded to the resin member and sealing the first space and the second space together with the resin member, The bonding region includes a roughened region formed on the surface, wherein the roughened region is formed with a base layer and a column group layer, wherein the base layer is a layer formed by accumulation of fragment particles, and the column group layer is a layer formed by two-dimensionally standing nano-columns in which the fragment particles are connected in a rosary-like manner and extend from the base layer in a height direction. The average height of the nano-columns in the roughened region is greater than or equal to 84 nm.
2. The metal component according to claim 1, wherein: The first space is arranged outside the joint area, and the second space is arranged inside the joint area. The bonding region is formed in a ring shape, and the roughened region is formed in a ring shape corresponding to the shape of the bonding region.
3. A metal-resin composite comprising: The metal member according to claim 1, and the resin member joined to the joining area, The resin forming the resin member fills the gaps between the nano columnar bodies until reaching the base layer.
4. A metal-resin composite comprising: The metal member according to claim 2, and the resin member joined to the joining area, The resin forming the resin member fills the gaps between the nano columnar bodies until reaching the base layer.
5. A method for manufacturing a metal component, which is the method for manufacturing a metal component according to claim 1 or 2, comprising: A laser irradiation step, wherein, on the surface of the metal component that can become the roughened area in a state where the column group layer has not yet been formed, fragment particles from the metal component generated by irradiation with pulsed laser are accumulated and grown into the nano-columnar bodies, thereby forming the roughened area.
6. A method for producing a metal-resin composite, the method for producing a metal-resin composite according to claim 3 or 4, comprising: a filling step of filling the hot melted molten resin into the gaps between the nano columnar bodies forming the column group layer until reaching the base layer; and and a curing step of curing the molten resin filled in the gaps between the nano columnar bodies forming the column group layer in the filling step to form a resin member bonded to the roughened region.
Citation Information
Patent Citations
Resin-metal joined body and pressure sensor
JP2018075805A